Carry a Torch for Your Enemy: Žižekian Study of Violence in Cormac McCarthy’s The Road (KEMANUSIAAN The Asian Journal of Humanities, 2020)
In Žižek’s belief, by the advent of capitalism in its global dimensions, violence took on different shapes and keeps on reshaping in various other forms. Things which decades ago were perceived as normal and nonviolent may render themselves today as harassment, violent and racist. For Žižek, “objective” violence within the system is the engine causing such violence. In a more challenging declaration, he contends that the global capitalist system is approaching an apocalyptic zero-point which will endanger environment and societies. This study aims to survey Žižek’s mentioned premise and also his theory of violence within Cormac McCarthy’s post-apocalyptic novel The Road. It will conclude by deducing that the world depicted in this novel could be regarded as a codicil to Žižek’s mentioned will. This deduction means that the way in which The Road features its dire reality, could be deemed a metaphor compatible with Žižek’s prognostication about the future of capitalism.